Forging the City Image during the French Colonial Period (1883-1962) in the Case of Jijel (Algeria) (Prostor, 2023)
The urban configuration of Algerian cities reflects the influence of French colonization (1883-1962). This is characterized by a collection of contrasts and overlays of different forms of architecture and urbanism. In all urban agglomerations in Algeria, the colonial section remains the most prominent and structured. This legacy of colonial architecture and urban planning has ignited a national debate in political and academic circles regarding its classification as heritage. This current study contributes to the debate by adopting a neutral and scientific approach in order to smooth things out and shed light on the role and creation of urban form and its image, specifically through the example of Jijel. The notion of urban image is explored through colonial architectural achievements, urban planning, and artistic endeavours that were emblematic of the city during the colonial period and continue to be so today. This article showcases various works created during the colonial period in Jijel, those that still convey an identity that defines the city. The concern for this identity is substantiated by a research project that seeks to identify the city's image through significant architectural works across different epochs and determine those that accurately convey the city's identity within the country.